Best practices for FAIR, ethical, and open data assets - CGIAR Platform for Big Data in Agriculture (2019)
The course modules have been drafted, revised, and input provided by a team of volunteer data and information specialists across CGIAR. The course will be interactive, to be uploaded for delivery via the TechChange platform. Course participants will need to sign in (free) to view or take the course.